A novel fluorescent retrograde neural tracer: cholera toxin B conjugated carbon dots. Issue 38 (18th August 2015) - Zhou, Nan; Hao, Zeyu; Zhao, Xiaohuan; Maharjan, Suraj; Zhu, Shoujun; Song, Yubin; Yang, Bai; Lu, Laijin
Abstract : Newly synthesised CTB-CD is a reliable fluorescent retrograde neural tracer and this is the first report about a new generation of neural tracer based on fluorescent nanoparticles. Abstract : The retrograde neuroanatomical tracing method is a key technique to study the complex interconnections of the nervous system. Traditional tracers have several drawbacks, including time-consuming immunohistochemical or immunofluorescent staining procedures, rapid fluorescence quenching and low fluorescence intensity. Carbon dots (CDs) have been widely used as a fluorescent bio-probe due to their ultrasmall size, excellent optical properties, chemical stability, biocompatibility and low toxicity. Herein, we develop a novel fluorescent neural tracer: cholera toxin B–carbon dot conjugates (CTB–CDs). It can be taken up and retrogradely transported by neurons in the peripheral nervous system of rats. Our results show that CTB–CDs possess high photoluminescence intensity, good optical stability, a long shelf-life and non-toxicity. Tracing with CTB–CDs is a direct and more economical way of performing retrograde labelling experiments. Therefore, CTB–CDs are reliable fluorescent retrograde tracers.